Evaluation of different buffer materials for solar cells with wide-gap Cu2ZnGeSxSe4−x absorbers. Issue 64 (16th August 2017) - Schnabel, T.; Seboui, M.; Bauer, A.; Choubrac, L.; Arzel, L.; Harel, S.; Barreau, N.; Ahlswede, E.
Abstract : In this work kesterite-type Cu2 ZnGeS x Se4− x (CZGSSe) absorbers were coated with four different buffer layer materials: CdS, In2 S3, Zn(O, S) and CdIn2 S4 . Abstract : In this work kesterite-type Cu2 ZnGeS x Se4− x (CZGSSe) absorbers were coated with four different buffer layer materials: CdS, In2 S3, Zn(O, S) and CdIn2 S4 . A detailed electrical characterization of the resulting solar cells was performed. The highest open-circuit voltage and the best band alignment could be reached with Zn(O, S), whereas the CdS buffer gave the best efficiencies of up to 6%, which is the highest reported efficiency for a CZGSSe absorber.